Good stability of a cementless, anatomically designed femoral stem in aging women: a 9-year RSA study of 32 patients. (3rd September 2018) - Aro, Erik; Alm, Jessica J; Moritz, Niko; Mattila, Kimmo; Aro, Hannu T
Abstract : Background and purpose — We previously reported a transient, bone mineral density (BMD)-dependent early migration of anatomically designed hydroxyapatite-coated femoral stems with ceramic–ceramic bearing surfaces (ABG-II) in aging osteoarthritic women undergoing cementless total hip arthroplasty. To evaluate the clinical significance of the finding, we performed a follow-up study for repeated radiostereometric analysis (RSA) 9 years after surgery. Patients and methods — Of the 53 female patients examined at 2 years post-surgery in the original study, 32 were able to undergo repeated RSA of femoral stem migration at a median of 9 years (7.8–9.3) after surgery. Standard hip radiographs were obtained, and the subjects completed the Harris Hip Score and Western Ontario and McMaster Universities Osteoarthritis Index outcome questionnaires. Results — Paired comparisons revealed no statistically significant migration of the femoral stems between 2 and 9 years post-surgery. 1 patient exhibited minor but progressive RSA stem migration. All radiographs exhibited uniform stem osseointegration. No stem was revised for mechanical loosening. The clinical outcome scores were similar between 2 and 9 years post-surgery. Interpretation — Despite the BMD-related early migration observed during the first 3 postoperative months, the anatomically designed femoral stems in aging women are osseointegrated, as evaluated by RSA and radiographs, and exhibit good clinical function at 9 years.